The Effect of Behavioral Management and Social Skills Training Program on Behavioral and Adaptive Problems of Male Adolescents with High-Functioning Autism - Leila Akrami; Malekpur Mokhtar; Salar Faramarzi; Ahmad Abedi (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective: The puberty and adolescence period is very important for adolescents with High-Functioning Autism (HFA). They require more education than their peers to understand the puberty period and the its associated changes. Parents' lack of knowledge of how to deal with adolescents correctly, lack of social skills and failure to provide adequate information to them  can create a variety of problems such as behavioral problems. The purpose of this study was to investigate the effect of a behavioral management and social skills training program on behavioral and adaptive problems  of male adolescent with HFA. Materials & Methods: The present study is a single-case study with ABA design. The statistical population consisted of male school students with HFA in Yazd, Iran. Of these, 3 were selected using purposive sampling method. By reviewing various papers related to behavioral problems, cognitive-behavioral approaches, Intervention Guide for Behavioral and Emotional Issues (IGBEI) and Intervention Guide of Social Skills Improvement System (IGSSIS), a program was developed for adolescents and their mothers. To evaluate the content validity of the program and to measure its reliability, Lawshe's method and Kappa coefficient were used, respectively. The program was presented in 37 sessions to the subjects and mothers. To collect data, the Behavior Assessment System for Children (BASC-3, parent and teacher rating scales) questionnaires was used and completed before and after the intervention. The collected data were analyzed using visual analysis indices and descriptive statistics.  Results: Raw data were first obtained for each participant in three phases of baseline, intervention, and follow-up and presented in the form of charts. Then, the stability and trend were plotted for all three participants at the baseline and intervention phases. Finally, using intra-situ and inter-situ analyses, the effectiveness of the educational program was evaluated. The results showed that the educational program was effective in reducing behavioral problems with Percent Non-Overlapping Data (PND) of 62.5% for the first and third subjects and 75% for the second subject, and increasing adaptive skills with a PND of 75% for the first and third subjects, and 87% for the second subject. Conclusion: Maternal and adolescent education based on an organized program can play an important role in reducing behavioral problems and enhancing adaptive skills during adolescence. Adolescents with HFA need more education to provide appropriate behavior due to the limitations; therefore, it is necessary to develop educational programs for this groups. One of the limitations of this study was the small size of samples; hence, generalization of results should be done with caution. Although many studies have been conducted in relation to children with HFA, further studies are recommended on these adolescents (male and female) in relation to their problems.